1992
DOI: 10.1093/rheumatology/31.11.759
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Collagen Crosslinks Reflect the Radiographic Severity of Knee Osteoarthritis

Abstract: The collagen crosslinks deoxypyridinoline and pyridinoline are indices of mature collagen breakdown and reflect increased bone turnover. Urinary levels were found to be significantly raised in a group of 59 women with knee OA compared to 110 female controls from the general population. Levels of the crosslinks correlated significantly with X-ray grade of all subjects including women from the general population with mild, often asymptomatic, disease. These correlations were not diminished after adjustment for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
21
0
1

Year Published

1994
1994
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 0 publications
3
21
0
1
Order By: Relevance
“…Kelman et al [8] recently showed increased serum levels of NTX I in an elderly female population in association with the onset of hip osteoarthritis. Similar findings were also described for the urine concentrations of DPD and CTX [2,22]. In our study we attempted to limit possible disturbing factors by creating a clear study protocol and recruiting a consistent study population.…”
Section: Discussionsupporting
confidence: 55%
“…Kelman et al [8] recently showed increased serum levels of NTX I in an elderly female population in association with the onset of hip osteoarthritis. Similar findings were also described for the urine concentrations of DPD and CTX [2,22]. In our study we attempted to limit possible disturbing factors by creating a clear study protocol and recruiting a consistent study population.…”
Section: Discussionsupporting
confidence: 55%
“…Although bone resorption is probably the major source of urine hydroxypyridinium cross-links [13,14], the PYD/DPD ratio may help to define collagen degradation in cartilage relative to other tissues. In agreement with previous studies in OA patients [10,13], PYD and DPD were highly correlated (r = 0.75, P < 0.001), and the PYD/DPD ratio was unchanged. In patients with advanced OA, both PYD and DPD were significantly increased and the PYD/DPD ratio was also unchanged.…”
Section: Discussionsupporting
confidence: 92%
“…Our number of normal controls is rather higher than that of previous studies, in some of which the same control group was used repeatedly [11,12,15]. Means and standard deviations of the present normal control group were also close to those of previous studies in which the same HPLC method was used [10,19]. There were more women and old patients in our OA group than in the control group.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…However, they suggested that increased urinary crosslinks may primarily originate from bone rather than cartilage. Tompson et al [23] have found urinary collagen crosslinks to be a weak marker of severity of knee OA. On the other hand, Astbury et al [24] and Graverand et al [25] have found no significant difference between OA patients and normals in urinary excretion of pyridinium crosslinks.…”
Section: Discussionmentioning
confidence: 99%